Older Adults’ Informal Learning Using Mobile Devices: A Review of the Literature - Bora Jin (Adult Education Research Conference, 2018)
This literature review will examine and critique literature concerning older adults’ use of mobile devices for informal learning. Findings have implications for adult educators and the barriers to the mobile device adoption among older adults for informal learning.
Keywords: mobile devices; older adults; informal learning